2001
DOI: 10.1021/bi0014498
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Glucagon-Like Peptide-1 Analogues in Vitro and in Vivo

Abstract: Studies support a role for glucagon-like peptide 1 (GLP-1) as a potential treatment for diabetes. However, since GLP-1 is rapidly degraded in the circulation by cleavage at Ala(2), its clinical application is limited. Hence, understanding the structure-activity of GLP-1 may lead to the development of more stable and potent analogues. In this study, we investigated GLP-1 analogues including those with N-, C-, and midchain modifications and a series of secretin-class chimeric peptides. Peptides were analyzed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
101
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(109 citation statements)
references
References 40 publications
8
101
0
Order By: Relevance
“…GLP-1 stimulates insulin secretion through modulation of the cAMP-PKA pathway [5,42], and in keeping with these findings, wortmannin treatment did not affect GLP-1-stimulated insulin secretion by the INS-1 cells. However, there is growing evidence that a number of hormones that signal through GPCRs can also activate cell growth and survival pathways, including GLP-1 (present study), GIP, the GLP-1-related intestinal hormone GLP-2 and parathyroid hormone-related protein (PTHrP).…”
Section: Discussionsupporting
confidence: 59%
“…GLP-1 stimulates insulin secretion through modulation of the cAMP-PKA pathway [5,42], and in keeping with these findings, wortmannin treatment did not affect GLP-1-stimulated insulin secretion by the INS-1 cells. However, there is growing evidence that a number of hormones that signal through GPCRs can also activate cell growth and survival pathways, including GLP-1 (present study), GIP, the GLP-1-related intestinal hormone GLP-2 and parathyroid hormone-related protein (PTHrP).…”
Section: Discussionsupporting
confidence: 59%
“…The residues that confer activity to soluble versus tethered ligands appear to share significant overlap (19). A previously published alanine scan of soluble GLP-1 demonstrated that H 1 and T 7 were among the important determinants of ligand function (20).…”
Section: Selected Amino Acids In the N-terminal Peptide Domain Definementioning
confidence: 99%
“…This compound stimulated cAMP production, insulin secretion, and lowered blood glucose concentration in Zucker fa/fa rats. Finally, it has been reported that substitution of L-alanine with D-alanine at position 8 of GLP-1 generates a DPP IV resistant peptide with insulinotropic and blood glucose lowering activities in db/db mice [139].Midchain modifications of GLP-1 have also been investigated with the expectation that such substitutions might improve the duration of action, potency, or efficacy. These expectations are based on the belief that the overall conformation of the GLP-1 peptide is strongly influenced by the midchain tertiary structure.…”
mentioning
confidence: 99%